From plants to nematodes: Serratia grimesii BXF1 genome reveals an adaptation to the modulation of multi-species interactions. Issue 7 (21st May 2018) - Nascimento, Francisco; Vicente, Cláudia; Cock, Peter; Tavares, Maria; Rossi, Márcio; Hasegawa, Koichi; Mota, Manuel
Abstract : Serratia grimesii BXF1 is a bacterium with the ability to modulate the development of several eukaryotic hosts. Strain BXF1 was isolated from the pinewood nematode, Bursaphelenchus xylophilus, the causative agent of pine wilt disease affecting pine forests worldwide. This bacterium potentiates Bursaphelenchus xylophilus reproduction, acts as a beneficial pine endophyte, and possesses fungal and bacterial antagonistic activities, further indicating a complex role in a wide range of trophic relationships. In this work, we describe and analyse the genome sequence of strain BXF1, and discuss several important aspects of its ecological role. Genome analysis indicates the presence of several genes related to the observed production of antagonistic traits, plant growth regulation and the modulation of nematode development. Moreover, most of the BXF1 genes are involved in environmental and genetic information processing, which is consistent with its ability to sense and colonize several niches. The results obtained in this study provide the basis to a better understanding of the role and evolution of strain BXF1 as a mediator of interactions between organisms involved in a complex disease system. These results may also bring new insights into general Serratia and Enterobacteriaceae evolution towards multitrophic interactions.